Comunidade fitoplanctônica em ambientes lóticos sob influência do Corredor de Biodiversidade Santa Maria, Bacia do Rio Iguaçu, Paraná, Brasil - Servat, Liliane Caroline (2015)
This work aimed to evaluate the influence of the riparian vegetation of Santa Maria Biodiversity Corridor on the structure and composition of the phytoplankton community, comparing two streams with different levels of riparian preservation: Apepu stream and Tenente João Gualberto stream. Samples were monthly collected, between September 2012 and August 2013. As a result, 371 taxa were identified, mainly benthic and periphytic taxa, belonging to the Classes Diatomeae and Euglenophyceae. An increase in the features density and species richness was observed from the Apepu stream (greater riparian bank) to the Tenente João Gualberto stream (smaller riparian bank. This fact may have been influenced by the shading caused by the riparian forest of station 1, since the nutrients concentrations of both environments were practically the same. However, despite showing lower values in the ecological attributes, Apepu stream presented a greater stability in the features and structure of the phytoplanktonic community during the study period. Besides, the greater equitability and similarity found in the first station indicate a greater homogeneity, when compared to Tenente João Gualberto stream. In summary, it was possible to demonstrate the importance of the riparian vegetation of Santa Maria Biodiversity Corridor for the stability of the phytoplanktonic community.